(untitled) (Justicia &Derecho, 2025)
The article examines the lack of regulation regarding the use of new technologies, particularly special artificial intelligence (AI) systems, within the framework of creditworthiness assessments as set out in Article 17 N of the Chilean Consumer Protection Act. It further analyzes the need to integrate this framework with current legal instruments and the pending bill aimed at regulating artificial intelligence in Chile.